2004
DOI: 10.2308/accr.2004.79.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Value-Glamour and Accruals Mispricing: One Anomaly or Two?

Abstract: We investigate whether the accruals anomaly is a manifestation of the glamour stock phenomenon documented in the finance literature. Value (glamour) stocks, characterized by low (high) past sales growth, high (low) book-to-market (B/M), high (low) earnings-to-price (E/P), and high (low) cash flow-to-price (C/P), are known to earn positive (negative) future abnormal returns. Note that “C” or cash flow is operationalized in the finance literature as earnings adjusted for depreciation. Sloan (1996) shows that fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
200
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(230 citation statements)
references
References 40 publications
24
200
3
3
Order By: Relevance
“…Consistent with this, Richardson et al (2004) find that analyst forecasts are more optimistic (pessimistic) for high (low) book-to-market firms. Second, high (low) accrual firms are likely to be glamour (value) firms (Desai et al 2004), so it could be argued that accruals proxy for growth, at least to some extent. 15 We also control for the analyst's outstanding stock recommendation, Recom, because prior literature finds greater analyst optimism for firms with hold/sell recommendations (Das et al 1998;Francis and Philbrick 1993).…”
Section: Empirical Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, Richardson et al (2004) find that analyst forecasts are more optimistic (pessimistic) for high (low) book-to-market firms. Second, high (low) accrual firms are likely to be glamour (value) firms (Desai et al 2004), so it could be argued that accruals proxy for growth, at least to some extent. 15 We also control for the analyst's outstanding stock recommendation, Recom, because prior literature finds greater analyst optimism for firms with hold/sell recommendations (Das et al 1998;Francis and Philbrick 1993).…”
Section: Empirical Predictionsmentioning
confidence: 99%
“…Recent studies examining the accrual anomaly suggests that research focusing on accrual mispricing without also considering cash flow mispricing is incomplete(Barone and Magilke 2009;Desai et al 2004;Yu 2007). Analysts' accrual-related over-optimism 61…”
mentioning
confidence: 97%
“…One group of studies relates accrual anomaly with other anomalies, such as the works of Collins and Hribar (2000), Desai, Rajgopal and Venkatachalam (2004), and Fama and French (2008). The first work identified that accrual anomaly is different than post-earnings announcement drift (the tendency for the cumulative abnormal returns of an asset to accompany an earnings surprise for various days after its announcement, due to an overreaction of the market to the result disclosed).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sloan (1996) showed that a hedge strategy with a long position in assets of low accruals and a short position in assets of high accruals generates significant abnormal returns. The accrual anomaly has been intensely debated in recent international academic literature in finance (Desai, Rajgopal, & Venkatachalam, 2004;Dopuch, Seethamraju, & Xu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…report there is strong and robust evidence that the level of accruals is a negative cross-sectional predictor of abnormal stock returns. Desai, Rajgopal, and Venkatachalam (2004), and Pincus, Rajgopal, and Venkatachalam (2007) both document that cash flows is an effective cross-sectional predictor of returns. Ndubizu (2007) reports that cross-listed firms have significant return on assets (ROA), cash flows, and working capital accruals that peak in the listing period, and decrease in subsequent years.…”
mentioning
confidence: 99%